2017
DOI: 10.1111/jac.12210
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and root characteristics of summer maize (Zea maysL.) under shade stress conditions

Abstract: Low light is a major adversity affecting yield and quality of summer maize in the Huang‐Huai‐Hai region of China. We conducted a field experiment to explore the effects of shading on root development and yield formation in two summer maize hybrids (Zea mays L.), Denghai605 (DH605) and Zhengdan958 (ZD958). The experiment consisted of four treatments (CK: ambient sunlight, S1: shading from tasselling to physiological maturity stage, S2: shading from six‐leaf to tasselling stage, S3: shading from seeding to physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 54 publications
(64 reference statements)
5
37
1
1
Order By: Relevance
“…This will help keep the carbon and nitrogen acquisition in tune. In accordance with these findings, direct shading in different phases of the growth period of field-grown maize was shown to suppress root mass, length, and absorptive area, suggesting reduced nutrient and/or water uptake rates (Gao et al, 2017). In addition to true shade, a reduced R: FR light ratio also affects root growth in different species Hunt, 1992, 1994;Salisbury et al, 2007).…”
Section: Functional Implications In Dense Vegetationsupporting
confidence: 62%
“…This will help keep the carbon and nitrogen acquisition in tune. In accordance with these findings, direct shading in different phases of the growth period of field-grown maize was shown to suppress root mass, length, and absorptive area, suggesting reduced nutrient and/or water uptake rates (Gao et al, 2017). In addition to true shade, a reduced R: FR light ratio also affects root growth in different species Hunt, 1992, 1994;Salisbury et al, 2007).…”
Section: Functional Implications In Dense Vegetationsupporting
confidence: 62%
“…In 2017, the SPAD value at 10 DAP only decreased in ZD958 and was unaffected in the other hybrids. The SPAD value at 20 DAP was unaffected in JY877, but the other three hybrids was decreased by shading, and the decrease was Plants 2020, 9,210 7 of 15 similar between MS and SS. At 30 and 40 DAP, the SPAD value was decreased by shading, and the decrease was severe under SS in all of the hybrids.…”
Section: Leaf Spad Valuementioning
confidence: 87%
“…ZD958: Zhengdan958; JY877: Jiangyu877; SY29: Suyu29; SY30: Suyu30. Values in the same year followed by different letters are significantly different (p < 0.05).Plants 2020,9, 210 6 of 15…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…For example, the numbers of cloudy/overcast/rainy days from early-June to mid-July in 2016 and 2017 in Yangzhou were 47 and 46, respectively (data available at http://www.tianq ihoub ao.com/lishi/ yangz hou.html). Studies have observed that postsilking shading decreases photosynthetic and electron transport rates Reed, Singletary, Schussler, Williamson, & Christy, 1988;Ren et al, 2016;Zhong, Shi, Li, & Huang, 2014), damages the leaf mesophyll cell ultrastructure (Ren et al, 2016), reduces the activities of enzymes involved in photosynthesis (Sharwood, Sonawane, & Ghannoum, 2014) and the activity of the carbon-concentrating mechanism with increased leakiness (Bellasio & Griffiths, 2014), affects the root morphology and activity indices (Gao, Shi, et al, 2017), increases the grain abscisic acid (ABA) content (Setter, Flannigan, & Melkonian, 2001), and reduces the endosperm cell number and volume (Jia, Li, Dong, & Zhang, 2011). These adverse effects reduce the dry matter and nutrient accumulation (Cui et al, 2013;Liu & Tollenaar, 2009;Mbewe & Hunter, 1986), increase aborted grain numbers due to the nearly halted filling of apical grains, and decrease grain weight (Cui, Camberato, Jin, & Zhang, 2015;Reed et al, 1988;Setter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%